Pemetaan Vektor (Jentik) Malaria Wilayah Eliminasi di Puskesmas Sidomulyo Kota Bengkulu - Moh. Gazali; Defi Ermayendri; Agus Widada (Poltekkes Kemenkes Bengkulu, 2025)
Malaria is an infectious disease transmitted by the Anopheles mosquito vector and is still a public health problem in Indonesia. The morbidity and mortality rates due to malaria are high, and have the potential to cause Extraordinary Events (KLB). The existence of malaria vectors is influenced by physical, biological, and socio-cultural environmental factors, so that control efforts require cross-sectoral and programmatic cooperation. Along with the national malaria elimination target in 2030, Bengkulu Province has had four districts/cities achieve elimination status, one of which is Bengkulu City. To maintain this status, strengthening environmental surveillance is crucial.This study aims to map the type and distribution of breeding sites and the presence of Anopheles sp. larvae in the working area of Sidomulyo Health Center, Bengkulu City. This study used spatial analysis with the help of Geographic Information System (GIS) to produce effective visualization and illustrate the relationship between ecosystem characteristics and vector presence. Coordinates of breeding sites were identified and the presence of Anopheles sp. larvae was observed.From the mapping results, 12 potential breeding sites were found, consisting of 6 ditches, 3 swamps, and 3 ponds. Four of them were confirmed positive for Anopheles sp. It is recommended that surveillance officers and malaria program managers conduct routine monitoring at positive sites as well as malaria screening for migrants from endemic areas who live temporarily or permanently in the Sidomulyo Puskesmas area.